SISTEM PENDUKUNG KEPUTUSAN UNTUK SELEKSI CALON PETUGAS SENSUS DI BADAN PUSAT STATISTIK KOTAMOBAGU MENGGUNAKAN TOPSIS - Rillya Arundaa (Journal of Engineering, Computer Science and Information Technology (JECSIT), 2022)
Census officers are one of the critical factors in census activities organized by the Central Bureau of Statistics. Qualified officers will produce a good performance in the agency and support the achievement of goals. Seeing the importance of the quality of officers, the candidate selection process is an important part and must be carried out immediately in the agency. The decision support system for selecting candidate census officers is expected to produce officers who meet the institution's criteria. The method used in this study is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). This method is one of the methods used to solve practical decision-making and can handle multi-dimensional problems in the selection of census officers. This research produces an application that provides user or users with recommendations. The recommendations given by the system are based on the assessment criteria and weighting criteria for each candidate census officer and then processed using TOPSIS to produce the best offers for the best candidate for the best census officer according to the ranking with the assessment parameters that have been determined according to the wishes/needs of the institution.